The Man Who Saw Tomorrow : The Life and Inventions of Stanford R. Ovshinsky - Hoddeson, Lillian; Garrett, Peter K. (Book collections on Project MUSE., 2018)
The first full-length biography of a brilliant, self-taught inventor whose innovations in information and energy technology continue to shape our world.